Software design and implementation of galvo mirror laser scanning - Trisno, Justin (Nanyang Technological University, 2022)
In recent years Confocal Laser Scanning Microscopy technique becomes more prominent in the field of biomedical imaging and material science. This is since the technique enables user to control the depth of field and eliminate or reduce the background information. This enables optical imaging in a better spatial resolution compared to the other techniques.